PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT (POS) TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIORAL (OCB) DENGAN EMPLOYEE ENGAGEMENT SEBAGAI VARIABEL MEDIASI (STUDI PADA KARYAWAN YAYASAN UKHUWAH BANJARMASIN) - Meta Ria Wati; Hastin Umi Anisah (Universitas Lambung Mangkurat, 2021)
This research aims to find out and analyze the influence of Perceived Organizational Support on Organizational Citizenship Behavioral, the effect of Perceived Organizational Support on Employee Engagement, and influence of Employee Engagement on Organizational Citizenship Behavioral of emplooyee at Ukhuwah Foundation Banjarmasin. This research is a quantitative research with an inferential statistics approach. This researcher used questionnaires with 167 respondens as the samples from 287 emplooyees using a simple random sampling technique. The measurement of variables used the Likert Scale technique with a weight scale from 1 of 5. The data analysis was used Partial Least Square (PLS). The result of this research indicated that (i) there was a significant positive influence of Perceived Organizational Support on Organizational Citizenship Behavioral, (ii) there was a significant positive influence of Perceived Organizational Support on Employee Engagement, (iii) there was a significant positive influence of Employee Engagement on Organizational Citizenship Behavioral, and (iv) Employee Engagament has partially mediated the influence of Perceived Organizational Support on Organizational Citizenship Behavioral